2017
DOI: 10.1007/s12035-017-0448-z
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol and Brain Mitochondria: a Review

Abstract: Resveratrol (3,4',5-trihydroxystilbene; CHO) is a polyphenolic phytoalexin found in grapes, berries, peanuts, and wines. Resveratrol has been viewed as an antioxidant, anti-inflammatory, anti-apoptotic, and anticancer agent. Moreover, it has been reported that resveratrol modulates mitochondrial function, redox biology, and dynamics in both in vitro and in vivo experimental models. Resveratrol also attenuates mitochondrial impairment induced by certain stressors. Resveratrol upregulates, for example, mitochond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
115
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(120 citation statements)
references
References 209 publications
3
115
0
2
Order By: Relevance
“…Thus, RES is a good candidate to prevent smoking-associated oxidative stress. Indeed, several studies have shown beneficial effects of RES on smoking in various organs (22)(23)(24), while the kidney is barely studied (10). Our study demonstrated that RES protected rat renal proximal tubule cells from NIC-mediated oxidative stress ( Figure 1B) by reducing ROS production ( Figure 1A).…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Thus, RES is a good candidate to prevent smoking-associated oxidative stress. Indeed, several studies have shown beneficial effects of RES on smoking in various organs (22)(23)(24), while the kidney is barely studied (10). Our study demonstrated that RES protected rat renal proximal tubule cells from NIC-mediated oxidative stress ( Figure 1B) by reducing ROS production ( Figure 1A).…”
Section: Discussionmentioning
confidence: 53%
“…Resveratrol (RES) is a naturally occurring antioxidant, found in high concentration in grapes and wine (21 production (22). Thus, RES is a good candidate to prevent smoking-associated oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Among the feasible mechanisms we suspect prooxidant activity resulting from formation of free-radical intermediates (such as aromatic radical cations) and/or interactions with transition metal ions, such as copper. The increasing oxidative molecules not only damage cell components directly but also release a cascade of responses in such organelles as ER or mitochondria [12,32]. The latter mechanism has been postulated as a major cause of cytotoxic properties of higher doses of polyphenols, useful for anticancer activity [32] but potentially harmful when cells must be protected (in neurodegeneration) [33].…”
Section: Discussionmentioning
confidence: 99%
“…Neurotoxicity-related cell damage is often associated with oxidative stress caused by mitochondrial energy impairment, which in turn initiates a chain of pathophysiological processes leading to cell death. Brain cells are prone to oxidative damage because of a high rate of oxygen consumption [12]. Oxidative stress (OS) also plays an important role in the 3-NP-induced neurotoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Other compounds have been used to stimulate mitochondrial biogenesis in cell and animal models of mitochondrial disfunction, including resveratrol ([19,20]) and retinoic acid ([21]), again with controversial results.…”
Section: Generalist Strategiesmentioning
confidence: 99%